2009
DOI: 10.3844/ajessp.2009.303.309
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Biodegradation of Per-Treated Methyl Tert-Butyl Ether By Ozonation in an Up-Flow-Fixed-Bed Reactor

Abstract: Problem Statement: MTBE is a common pollution of environmental and has become an issue of considerable concern in recent years. It is not readily amenable to remove MTBE by conventional techniques in water treatment. In the present study, the feasibility of the continuous aerobic biodegradation of MTBE, was evaluated in an Up-Flow Fixed Bed Reactor (UFBR). Approach: The UFBR at a constant Hydroulic Retention Time (HRT) of 24 h was used as a biological process that receives the intermediates due to partial oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Ghaforyan et al, has shown that, the transfer ratio is defined as the ratio of electron emission current I e to the circulating current I c for a given voltage applied across the sandwich. Results of such experiments indicated a strong attenuation of electrons in the top metal electrode and also provided evidence of inelastic interactions of the injected electrons in the top layer (Hickmott, 1962;Ilyas and Hogarth, 1983;Mordvintsev et al, 1998;Ray and Hogarth, 1985;Sharpe and Palmer, 1996;Silva et al, 2001;Simmons, 1963a;1963b;Thurstans and Oxley, 2002;Reda, 2010;Iskandarani, 2010;Fen et al, 2011;Al-Saqer et al, 2010;Sadeghi et al, 2009).…”
Section: Introductionmentioning
confidence: 95%
“…Ghaforyan et al, has shown that, the transfer ratio is defined as the ratio of electron emission current I e to the circulating current I c for a given voltage applied across the sandwich. Results of such experiments indicated a strong attenuation of electrons in the top metal electrode and also provided evidence of inelastic interactions of the injected electrons in the top layer (Hickmott, 1962;Ilyas and Hogarth, 1983;Mordvintsev et al, 1998;Ray and Hogarth, 1985;Sharpe and Palmer, 1996;Silva et al, 2001;Simmons, 1963a;1963b;Thurstans and Oxley, 2002;Reda, 2010;Iskandarani, 2010;Fen et al, 2011;Al-Saqer et al, 2010;Sadeghi et al, 2009).…”
Section: Introductionmentioning
confidence: 95%